Development and pilot evaluation of a virtual environment for assessment of way-finding ability in persons with neurological disability. - Reid D; Wan C; Hebert D (Technology & Disability, 2009)
This paper describes a new computerized test called Virtual City© designed to assess way-finding skills in persons with neurological problems. Virtual City is based on the theoretical premise that a left brain (verbal cognition) model and a right brain (visual spatial) model are important to the study of way-finding through two process-based modules, a visual map and verbal instructions. Preliminary work that assessed the clinical utility and validity of Virtual City is reported. Twenty-six healthy adults and nine adults with neurological damage completed the two test modules: map following (visual spatial), and reading instructions (verbal ability), on two separate occasions. The results suggest that individuals with neurological damage require more time to complete both modules (map: 282.46s; reading: 410.31s) when compared to healthy adults (map: 275.99s, reading: 221.23s). These results confirm the declined cognitive resources available to person's with neurological damage. However, the suggested right-left brain hypothesis in relation to brain lesion site in the neurological population and performance pattern remains questionable. These preliminary findings suggest that Virtual City shows promise in differentiating adults with neurological damage from healthy adults. Individual data analyses suggest that clinicians may be able to identify whether certain patients tend to rely more of visual or verbal cues. This information may assist them to develop more effective rehabilitation strategies. More research is needed to confirm whether there is a clear right-left bias involved in performing virtual way-finding tasks.